2017
DOI: 10.1016/j.ijpara.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of the IId subtype family of Cryptosporidium parvum

Abstract: Host adaptation is known to occur in Cryptosporidium parvum, with IIa and IId subtype families preferentially infecting calves and lambs, respectively. To improve our understanding of the genetic basis of host adaptation in Cryptosporidium parvum, we sequenced the genomes of two IId specimens and one IIa specimen from China and Egypt using the Illumina technique and compared them with the published IIa IOWA genome. Sequence data were obtained for >99.3% of the expected genome. Comparative genomic analysis iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 29 publications
6
63
1
Order By: Relevance
“…In Cryptosporidium species, differences in copy numbers of genes encoding SKSR proteins have been observed between C. parvum IIa and IId subtype families [17]. The subtelomeric genes encoding these SPDs, except for those encoding WYLE proteins, are mostly lost in C. bovis and C. ryanae.…”
Section: Discussionmentioning
confidence: 99%
“…In Cryptosporidium species, differences in copy numbers of genes encoding SKSR proteins have been observed between C. parvum IIa and IId subtype families [17]. The subtelomeric genes encoding these SPDs, except for those encoding WYLE proteins, are mostly lost in C. bovis and C. ryanae.…”
Section: Discussionmentioning
confidence: 99%
“…WGS analysis of Cryptosporidium spp. has further indicated that copy number variation in two subtelomeric gene families encoding secreted MEDLE proteins and insulinase-like peptidases is involved in differences in host specificity between C. parvum and C. hominis and among host-adapted C. parvum subtype families (Guo et al, 2015c ; Liu et al, 2016 ; Feng et al, 2017 ).…”
Section: Molecular Epidemiologic Toolsmentioning
confidence: 99%
“…Overall, gene content and genomic organisation among intestinal occurrences of the species are well conserved, with Cryptosporidium gene clusters encoding putative secreted proteins. Comparison of the Cryptosporidium genomes has identified a core set of proteins commonly studied, as well as major differences in particular gene families, which could be involved in biological differences between species and genotypes [114,[183][184][185]. Gene encoding proteins that are associated with invasion processes, e.g.…”
Section: Genome Of Cryptosporidium: New Insight and Future Challengesmentioning
confidence: 99%